Analisis Kelayakan Implementasi Sistem Informasi Manajemen berbasis Cloud Computing pada Industri Pedagangan Online - Mintawati, Hesri; Simangunsong, Bonse Aris Mandala Putra; Suhardi, Mulyadi; Sukma, Novia Indah; Fasha, Zahra Aprili; Herdiansyah, Moch Fachreza (JUDICIOUS, 2023)
The advancement of technology has led to the widespread adoption of Cloud Computing in various industries, including online trading. This research aims to analyze the feasibility of implementing a Cloud Computing-based Management Information System (MIS) in the online trading industry. Using a qualitative and quantitative approach, the study examines the infrastructure, security, cost, and benefits associated with the implementation of such a system. A case study of a leading cloud hosting provider in the industry was conducted to gather data through interviews, questionnaires, observations, and document analysis. The results indicate that the implementation of a Cloud Computing-based MIS is feasible and offers significant benefits, including improved operational flexibility, scalability, and data accessibility. However, challenges such as data security and integration with existing systems need to be addressed. This research contributes to the understanding of the potential of Cloud Computing in enhancing management information systems in the online trading industry.